1995
DOI: 10.1007/bf01682036
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase-release assay: A reliable, nonradioactive technique for analysis of cytotoxic lymphocyte-mediated lytic activity against blasts from acute myelocytic leukemia

Abstract: Treatment of patients in remission of acute myelocytic leukemia using immunotherapy with interleukin 2 is a new approach to prolonging remission duration in this disease. As an important mechanism for the pathophysiology of eradication of residual myelocytic blast populations, activation of cytotoxic effector lymphocytes has frequently been discussed. However, the associated immunological research has been complicated to some extent, because in conventional chromium 51-release assays, blast cells frequently fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…The activity of LDH released into culture medium was determined by the enzyme-coupled color development method as previously described (Weidmann et al, 1995) with minor modifications. In brief, cells were exposed to NMDA or other compounds, and further cultured for an additional 24 h in DMEM without phenol red.…”
Section: Lactate Dehydrogenase (Ldh) Release Assaymentioning
confidence: 99%
“…The activity of LDH released into culture medium was determined by the enzyme-coupled color development method as previously described (Weidmann et al, 1995) with minor modifications. In brief, cells were exposed to NMDA or other compounds, and further cultured for an additional 24 h in DMEM without phenol red.…”
Section: Lactate Dehydrogenase (Ldh) Release Assaymentioning
confidence: 99%
“…Cytotoxicity of splenic MNC (the effector cells collected from the spleen using the procedure described for LAI) against target cells (EAC cells) was tested in a lactate dehydrogenase (LDH) release assay using the LDH-FS non-radioactive cytotoxicity assay kit (DiaSys Diagnostic Systems GmbH, Germany) following the procedure of Weidmann et al [40]. Effector as well as target cells were washed separately in 15-ml centrifuge tubes with PBS and their pellets were dissolved separately in phenol red-free RPMI 1640 (HiMedia) medium.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, (1) the proliferation indices of T cells were assayed by CFSE-staining method with flow cytometry [32,33], which showed that the BCG HSP70 gene transfected AML/B-ALL cells significantly enhanced lymphocyte proliferation; (2) cytokine level by ELISA suggested that HSP70-transfected AML/B-ALL cells stimulated autologous T cells to secrete the highest cytokine level (IFN-γ); (3) lactate dehydrogenase (LDH) release assay used to measure killing activity of CTLs [34] showed that the killing rate of CTL in the group of HSP70-transfected AML/B-ALL cells was significantly higher than that of the wide-type AML/B-ALL cells and pDisplay-transfected ones, suggesting that BCG HSP70 gene transfection could significantly enhance the killing activity of autologous CTL on leukemia cells.…”
Section: Discussionmentioning
confidence: 99%